Study Teologis Makna Sabar Sebagai Bagian Panggilan Pelayanan Pastoral Menurut Surat 2 Timotius 4:1-8 - Paulus Kunto Baskoro; Yemima Erma Kristiani (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2023)
Pastoral ministry requires patience. This research focuses on a pratical theological approach in believing that calling to Christ can be realized from an understansing and awareness of the meaning of “patience” itself which helps encourage believers to carry out theological prinsiples with confidence, encouragement and joy. So that the congregation served feels comfortable and grows more spiritually. The method used is decriptive qualititative method of Paul’s second letter to Timothy realting to the growth of Christian faith and calling to serve. Research is assessed based on several understandings trough book or literature. This paper has several objectives, namely : First, to describe the meaning of the word patient in general and its teological approach. The second, explains the praxia-teological implacations as the fundatuion of true understanding in the Christian faith. The conclusion of this research is that every church leader or pastor patiently serves the pastoral ministry and focuses on making every pastoral soul mature and grow spiritually.